Arid Climate Conditions Vs Water Resources Management in Africa Based on the Sustainable supply chain operations - Mohamed Hamdy ElKomy (International Journal of Supply Chain Management, 2020)
Abstract-The purpose of this paper is to explore the impact of sustainable supply chain operations on economic, environmental and social performance, which are the three dimensions of corporate sustainability. Africa has been subjected to water stress due to its large part in arid and semi-arid geographical areas and its topographical features and uneven temporal and spatial distribution of rainfall. In this research, an attempt was carried out for water resources management in an arid climate area, the area is the central part of Darb El Arbeain. The study area occupies the central area of Darb EL-Arbeain and bounded by long. 30o 15/ and 30o 25/ E and lat. 23o 55/ and 24o 05/ N, it has an area of about 120 Km2. In this study four suggested exploitation rates of groundwater have been explored using the three-dimensional finite difference flow model (MODFLOW 2005) to simulate the flow system. These scenarios include running the model with abstraction from the aquifers equal 110 %, 180 %, 280 %, and 370 % of calculated initial recharge. The results indicated that the equilibrium could be reached while pumping out from the aquifer in that arid climate area, and the drawdown could be stable after some time depending on the potentiality and heterogeneity of the aquifer.